2013
DOI: 10.1097/sap.0b013e3182305e96
|View full text |Cite
|
Sign up to set email alerts
|

The Tropical Diabetic Hand Syndrome

Abstract: Tropical diabetic hand syndrome (TDHS) is an aggressive type of hand sepsis that results in significant morbidity and mortality among patients with diabetes in the tropics. This study set out to establish a protocol for the holistic management of TDHS to improve digit/hand salvage and function at AIC Kijabe Hospital. This prospective study examined the following demographics of patients presenting to the authors institution between October 2009 and September 2010 with TDHS: their sex, age, comorbidities, lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
9
0
4
Order By: Relevance
“…2,4 TDHS is an aggressive type of hand sepsis that results in significant morbidity and mortality among patients of diabetes in the tropics. 10 TDHS has also been reported among diabetic patients in the Indian subcontinent. 7,8 The present case also belongs to a beautiful and naturally gifted part of the subcontinent, the Kashmir valley.…”
Section: Discussionmentioning
confidence: 94%
“…2,4 TDHS is an aggressive type of hand sepsis that results in significant morbidity and mortality among patients of diabetes in the tropics. 10 TDHS has also been reported among diabetic patients in the Indian subcontinent. 7,8 The present case also belongs to a beautiful and naturally gifted part of the subcontinent, the Kashmir valley.…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with data reported by other centers, S. aureus was the most commonly identified pathogen in culture overall. [18][19][20][21][22][23] The etiologic agents of hand infection were comparable between the DM and no-DM groups: rates of identification of all S. aureus, MRSA, gram-negative organisms, and polymicrobial cultures did not differ significantly between DM and no-DM groups. The literature describes the rates of culture of gram-negative organisms from hand infections as ranging from 51.1 to 73% in diabetics and 8 to 11.3% overall.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reports related to hand infections in diabetes are from developing countries in the tropical world and it is defined as diabetic hand syndrome with musculoskeletal manifestations such as limited joint mobility, Dupuytren's contracture, and trigger fingers (10,11,(13)(14)(15)17,19,21,24,31,37,40,41). Diabetes and related complications are common in Turkey but only three studies about hand complications related to diabetes from this country were found in the literature (2,6,20).…”
Section: Discussionmentioning
confidence: 99%
“…Late admission to hospital reduced the success of the treatment (10,13,20,21,27,36). The rate of late admission was 96.97% and the mean time for admission was 1.38 weeks in our review of the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation